International normative commitments to multi-ethnicity: the case of Kosovo, 1999-2012 - Landau, DM (2016)
Following the war in Kosovo in 1999, the international community embarked on the most extensive international peace- and state-building project to date. From the early UN administration of Kosovo until the end of ‘supervised independence’ in 2012, various international organisations played a critical role in shaping the post-war polity. Throughout this engagement, the international community was driven by normative commitments to multi-ethnicity. However, while international organisations were committed to making Kosovo ‘multi-ethnic’, lack of clarity prevailed about what this goal entailed, or why it was so important. The thesis seeks to answer two inter-related questions: what was meant by multi-ethnicity on the part of its proponents, and what explains the prominence of commitments to this idea. Taking the form of three sections, the thesis examines these commitments’ origins, manifestations, and explanations. International normative commitments to multi-ethnicity are found to originate in a shifting conception of the relationship between ethnic diversity and legitimate statehood during the twentieth century. Their manifestations in Kosovo are studied in three policy domains: the return of displaced persons, decentralisation of government to the local level, and minority rights. The thesis finds that international efforts in the pursuit of multi-ethnicity in Kosovo exhibited conflicting notions of multi-ethnicity, which shifted from integrationist ambitions to notions that reconciled the reality of segregation between ethnic groups on the ground through a ‘politics of recognition’. The goal of multi-ethnicity remained, but was transformed. Explanations for the commitments to multi-ethnicity are found in both normative and consequentialist considerations, by uncovering unspoken underlying assumptions, and in the identity and self-image concerns of international actors. These findings indicate the power of the normative environment in shaping the actions of international organisations and provide insights into the thus far under-theorised normative dimension of the international state-building project in Kosovo.